2012
DOI: 10.1039/c2ja30162h
|View full text |Cite
|
Sign up to set email alerts
|

In situ analysis of 230Th–232Th–238U ratios in titanite by fs-LA-MC-ICPMS

Abstract: The potential of femtosecond laser ablation multi-collector inductively coupled plasma mass spectrometry (fs-LA-MC-ICPMS) for in situ analysis of U-Th disequilibria in titanite was investigated. The aim of the study was to resolve spatial variations in ( 230 Th/ 238 U) ratios (where parentheses denote activity) in titanite from slowly cooled magma bodies. An in-house titanite glass (TG2), determined to be in secular equilibrium by solution mode MC-ICPMS (i.e. ( 230 Th/ 238 U) ¼ 1), was used to correct for U-Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 47 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…It was hoped that the development of the femtosecond laser would also limit the degree of fractionation (Horn and von Blanckenburg 2007). A recent study of U-Th disequilibria in sphene using a femtosecond laser has shown that while the 230 Th/ 232 Th ratios could be measured accurately, it was more difficult to obtain precise results on Th/U ratios if the standard compositions did not match the matrix of the natural samples (Koornneef et al 2012). Thus, an important conclusion from this research is that the production of high quality standards of equivalent composition and texture seems essential.…”
Section: à7mentioning
confidence: 97%
“…It was hoped that the development of the femtosecond laser would also limit the degree of fractionation (Horn and von Blanckenburg 2007). A recent study of U-Th disequilibria in sphene using a femtosecond laser has shown that while the 230 Th/ 232 Th ratios could be measured accurately, it was more difficult to obtain precise results on Th/U ratios if the standard compositions did not match the matrix of the natural samples (Koornneef et al 2012). Thus, an important conclusion from this research is that the production of high quality standards of equivalent composition and texture seems essential.…”
Section: à7mentioning
confidence: 97%
“…Uranium-series analytical measurements are widely used in geochemistry and geochronology , and can be applied to a wide variety of fields including paleoclimatology, , volcanology, , environmental risk assessment, , and archeology. , Recent advances in high-resolution, rapid, in situ, microanalytical techniques, for example, laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS), secondary ion mass spectrometry (SIMS), and micro X-ray fluorescence (μ-XRF) present numerous opportunities for the analytical community. Reference glasses are essential in microanalysis and are commonly used as samples for calibration, method development, quality control/assurance, and for inter-laboratory comparison . About 20–25 reference glasses are currently available for microanalysis .…”
mentioning
confidence: 99%